(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Otitis media is a group of complex inflammatory disorders affecting the middle ear, which can be acute or chronic. Otitis externa is an inflammation on the skin of the external auditory canal usually associated with secondary bacterial and/or fungal infection of macerated skin and subcutaneous cellular tissue. Objective: To investigate the effect of ginger extracts on fungal isolates from patients suffering from otitis. Methods: Two hundred patients suffering from suppurative otitis media and externa who attended to ENT Department, Al-Imamein Al-Kadhimein Medical City enrolled in this study from November 2016 to the end of April 2017, included patients all age groups with discharging ear. All specimens were transported to the laboratory for processing and investigations at the same day. The powder of ginger rhizomes soaked with the solvent and left in a shaking water bath at 40 °C for 24 hours, and then filtered using Whatmann’s filter paper No.1 for clear extract. Each extract was concentrated using a rotary evaporator with vacuum to get the final crude extract after the procedure of ginger extract was done, this extract was taken and tested for bacterial and fungal isolates from patients with otitis. Results: Results revealed that acute otitis media consisted of about 96 (48%), while chronic suppurative otitis media about 75 (37.5%). Otitis externa was less common infection among the other types of otitis 29(14.50%). The most fungal isolates were Candida parapsilosis. In addition, there is a significant effect of (chloroform, methanol, and aqueous) extract of ginger on pathogenic fungi. Conclusion: Ginger extracts have been showed evident zones of inhibition effect on pathogenic fungi by chloroform more than ethanol, with less effect by aqueous extract. Keywords: Otitis externa, otitis media, ginger extract Citation: Al-Attraqchi AAF, Sahib HB, Al-Hasseni JMK, Mohammed MM. The vitro study effect of ginger extracts on fungal isolated from a suppurative otitis media and externa. Iraqi JMS. 2019; 17(1): 4-11. doi: 10.22578/IJMS.17.1.2